Multi-dimensional aspects of poverty and their linkages amongst squatters in Kampong Baru Stutong, Tabuan Jaya, Kuching / Wee Chong Hui, Rosita Suhaimi and Annie Wong Muk Ngiik - Wee, Chong Hui; Suhaimi, Rosita; Wong, Annie Muk Ngiik (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This is a study on a multi-dimensional aspects of poverty. It attempts to find out the linkages amongst squatters in Kampong Baru, Kuching and their relationships with expenditure, nutrition, housing and access to piped water, electricity, sewage and income.